Proceedings XXV Ciosta-CIGR V Congress : Farm planning, labour and labour conditions, computers in agricultural management - Annevelink, E.,; Oving, R.K,; Vos, H.W., (Biology - Book Archive pre-2000, 1993)
This publication contains the papers accepted for the XXV CIOSTA-CIGR V Congress, held in Wageningen, The Netherlands, May 10-13, 1993. The congress is being held under the auspicies of four Dutch organizations all of which are closely connected with agriculture. The proceedings provide an overview of research in the field of agricultural labour and farm management. The focus of interest in agricultural labour research has shifted from the more efficient use of labour as a factor of production to the conditions in which labour works. In many countries, labour, including agricultural labour, is under stress. Approaches to farm management are becoming increasingly sophisticated utilizising complicated mathematical applications. Some of these applications have already been introduced to farmers, software development continues and it is important that they be implemented in practise.